RNA and protein expression analysis of HLA‐DQB1*03:01:01:21Q allele: A null allele renamed as HLA‐DQB1*03:01:01:21N. (17th January 2022) - Marin Rubio, Luis Alberto; Aroca‐Aguilar, Jose Daniel; Luis‐Hidalgo, Mar; Escribano, Julio; Ontañon, Jesus
Abstract : The characterization of the expression profile of HLA questionable alleles (Q) is clinically relevant in allogeneic hematopoietic stem cell transplantation (HSTC) because an aberrant expression of these alleles could lead to transplantation‐related complications. HLA‐DQB1*03:01:01:21Q shows a substitution at the donor splice site of intron 3 that potentially could affect the expression of this allele. In order to determine their expression profile at RNA and protein level, we analyzed the presence of the HLA‐DQ7 molecule by complement‐dependent cytotoxicity test (CDC) and flow cytometry, and their RNA processing by cDNA analyses and sequencing by Sanger methods. Our results reveal that HLA‐DQ7 is not detectable by serological methods, this is confirmed by cDNA methods demonstrating the absence of specific HLA‐ DQB1*03:01:01:21Q mRNA, probably due to an intron 3 retention that creates a premature TGA stop codon, leading to mRNA degradation via nonsense‐mediated decay (NMD). These findings demonstrate that the HLA‐DQB1*03:01:01:21Q allele is nonexpressed, thus it has been renamed as DQB1*03:01:01:21N .